Perbandingan Kekuatan Hukum Alat Bukti Otentik dan Perjanjian Bawah Tangan (Studi Kasus Perkara nomor: 939/Pdt.c./2818/Pn dps) - I Made Indra Udayana; Made Minggu Widyantara; Ni Made Sukariyati Karma (Warmadewa Press, 2021)
Law is a rule of life that regulates human life in society, as a rule of life, the law functions to limit the interests of each legal supporter (legal subject), guaranteeing their respective interests and rights. The purpose of this study is to determine the comparison of the legal strength of authentic deed evidence with private deed, as well as to determine the judge’s considerations in his decision on the legal strength of private deed which defeats authentic deed. This research is a type of normative legal research conducted by recording and reviewing methods based on legal materials, while the problem approach uses a statutory and conceptual approach. The source of the data obtained from this research is by looking for accurate information by studying the symptoms of the community in order to get the actual data, thus the data obtained can be combined with several legal book references related to research. The results of the study show that the comparison of the legal strength of authentic deed evidence with an underhand deed, namely the deed is made by or before an authorized official in his working area as regulated by law and is perfect evidence as contained in Article 1870 K UHPer.